The minor victim of crimes: family maltreatment in the Kingdom of Italy (Italian Review of Legal History, 2019)
The criminal protection of the minor has a relatively recent history.The first code that involved the minors was that of Napoleon: the protection was prepared since the pregnancy through crimes such as procured abortion and infanticide but the normative corpus was silent on any mistreatment of parents towards their children.Also in the pre-unification codifications there are no signs of this crime. The only exception was the Sardinian codex of 1839 which provided for the crime of cattivi trattamenti between spouses. In the newest version of the Albertino code of 1859, it proposed to sanction "the excesses in the correction that could be committed by the fathers towards their children": the innovative crime expounded by art. 560 showed itself as a true ancestor of today's crime of "abuse of the means of correction".In 1873 the Canton Ticino Code was issued: it was almost a copy of the preparatory works of 1868 of the first Italian penal code. For this reason it introduced the crimes of maltreatment in the family and of abuse of the means of correction on which the Italian jurists were already busily working. In reality, already the previous 1816 code provided for the case of excess coercion which referred to the conduct of artisans, bosses and employers towards their subordinates.The crime of family maltreatment was officially introduced in Italy in art. 391 of the Zanardelli code as a crime halfway between injury and injury. The conduct, in fact, could crystallize in the presence of behaviors harmful both from the psychological and physical point of view. Both the mistreatment and the abuse of the means of correction were included in the crimes against the person, abridging the approach - still close to the mentality of the ancient regime - which typically incardinated them, still at the beginning of the XIX century, in the crimes against the family.The crime of abuse of the means of correction, foreseen by the 1889 code to the art. 390, it was proposed as an intent to protect the minor from a conduct that was in itself lawful but was abused by the parent. A protected juridical good in this case was not only the physical integrity of the minor but also his right to cohabitation.With the rise to power of fascist politicians, the whole society was influenced by the regime: the centrality of the social function of the family in the State to the point pushed doctrine and, sometimes, jurisprudence to start a fervent debate about the public or private placement of the sub-system. Antonio Cicu brought family law closer to the public one due to the analogy of the structure of the legal relationship between the two branches of the order. The crime of family maltreatment, provided by the art. 572, was placed in the title XI dedicated to the "Crimes against the family" in the head of the "Crimes against family assistance" and no longer in those against the person, as instead preferred by the previous Zanardelli code. This position reflected the centrality of the family in the construction of fascist society. The distinctive criterion with the crime of abuse of the means of correction remained the same endorsed in the doctrine during the validity of the Zanardelli code, that is, it was based on the animus of the active subject.The growing attention, in the legal culture between the nineteenth and twentieth centuries, to the figure of the minor had repercussions even in the nascent criminological sciencesin particular because of the growing importance assumed by the phenomenon of abandonment, whose links with criminal delinquency were the subject of important cornerstones of the literature of the time.It is for this reason that the Rocco code, in art. 591, sanctioned the abandonment of minors by cataloging the crime among those against life and individual safety.The recognition of the binomial ‘rights of minors - duties of parents’ inevitably overwhelmed age-old penal incrustations, attributing to the State a predominant role in the establishment and management of places of assistance and / or charity where “protecting the small pariahs of life”. The public administration took charge of the reparative task on behalf of the company, which had also been guilty of the first crime against children.
Keywords: Family; Minors; Ius corrigendi; Domestic violence